Method for producing RTB-based sintered magnet and RTB-based sintered magnet

By using the non-lively gas after using the humidified non-lively gas when the sintering magnet of the sintering is sintered, the oxygen content is controlled within a specific range, and the problem of low crushing efficiency and the decline in magnetic specialty are solved, and high performance and efficient crushing are achieved.

CN114867572BActive Publication Date: 2025-01-24PROTERIAL LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080089947.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-24
Filing Date
2020-12-24
Publication Date
2025-01-24
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

When manufacturing the R-T-B system sintered magnet, in order to reduce the oxygen content and prevent the oxidation of the powder particles, spray grinding is performed using high-purity nitrogen, but it is difficult to achieve the expected high performance and the crushing efficiency will decrease.

Method used

By using the non-lively gas after using humidifying during the spray grinding process, the microfilling of the R-T-B-based sintering magnet is crushed, and the content of the oxygen control is less than 3500 ppm or less, and the micro-fineization and high performance of the powder particles are achieved.

Benefits of technology

This method can inhibit the deterioration and oxidation of the powder particles during the crushing process, improve the crushing efficiency, and obtain a sintering magnetic R-T-B-based sintering magnet with excellent magnetic specialty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114867572B_ABST
    Figure CN114867572B_ABST
Patent Text Reader

Abstract

The manufacturing method of the R-T-B system sintered magnet of the present invention includes: a process of preparing a coarsely crushed powder of an alloy for R-T-B system sintered magnet with an average particle size of not less than 10μm and not more than 500μm; a process of supplying the above-mentioned coarsely crushed powder to a jet mill device whose crushing chamber is filled with an inert gas and crushing the above-mentioned coarsely crushed powder to obtain a fine powder with an average particle size of not less than 2.0μm and not more than 4.5μm; and a process of preparing a sintered body of the above-mentioned fine powder, the above-mentioned inert gas is humidified, and the oxygen content of the above-mentioned R-T-B system sintered magnet is not less than 1000ppm and not more than 3500ppm in terms of mass ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a RTB based sintered magnet and the RTB based sintered magnet. Background Art

[0002] RTB based sintered magnets (R is a rare earth element and must contain at least one selected from Nd, Pr and Ce, T is at least one transition metal and must contain Fe, and B is boron) are composed of R 2 Fe 14 The main phase of the compound with B-type crystal structure, the grain boundary phase located at the grain boundary of the main phase, and the compound phase generated by the influence of trace added elements or impurities, show high residual flux density B r (hereinafter sometimes referred to as "B r ”) and high coercivity H cJ (hereinafter sometimes referred to as "H cJ ”) and has excellent magnetic properties, so it is known to be the highest-performance magnet among permanent magnets. Therefore, it has been used in a variety of applications such as voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV), motors for industrial equipment, and various other motors and home appliances.

[0003] Such an RTB based sintered magnet is produced, for example, through the steps of preparing alloy powder, compacting the alloy powder to produce a powder compact, and sintering the powder compact. The alloy powder is produced, for example, by the following method.

[0004] First, an alloy is produced from a melt of various raw metals by a method such as an ingot casting method or a thin strip continuous casting method. The obtained alloy is subjected to a pulverization step to obtain an alloy powder having a predetermined particle size distribution. The pulverization step generally includes a coarse pulverization step and a fine pulverization step, the former being performed, for example, by utilizing the hydrogen embrittlement phenomenon, and the latter being performed, for example, by utilizing an airflow pulverizer (jet mill).

[0005] The alloy powder obtained in the pulverization step is subjected to solid-gas separation using, for example, a cyclone collector, to recover (collect) the alloy powder for RTB based sintered magnet.

[0006] RTB-based sintered magnets are required to have higher performance and lower costs. Methods for improving performance include, for example, miniaturization of the structure and reduction of oxygen content; methods for reducing costs include, for example, improving the pulverization efficiency. Patent document 1 discloses, as a method for improving pulverization efficiency, a method of jet mill pulverization using an inert gas flow humidified to a dew point of -20°C to 0°C. The same method is also described in Patent document 2.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 8-148317

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 6-140220 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] In the production of R with a reduced oxygen content, for example, an oxygen content of 3500 ppm or less by mass ratio 2 T 14 In the case of an RTB based sintered magnet having the B phase as the main phase, in order to prevent oxidation of powder particles during the pulverization step, for example, high-purity nitrogen gas may be used as the inert gas.

[0013] According to the research of the inventors of the present invention, when jet milling is carried out using an inert gas such as high-purity nitrogen, the expected high performance may not be achieved in the case of low oxygen. In addition, when the powder is miniaturized to achieve high performance, the miniaturization will sacrifice the pulverization efficiency. Regarding the pulverization efficiency, there are also methods disclosed in Patent Documents 1 and 2, but the structures disclosed in Patent Documents 1 and 2 are technologies that achieve a high oxygen content of more than 4500ppm in order to suppress reactivity, and cannot be applied to the high performance brought about by low oxidation. The embodiments of the present invention provide a method for manufacturing an RTB-based sintered magnet and an RTB-based sintered magnet that can solve such problems.

[0014] Technical solutions for solving technical problems

[0015] In a non-limiting exemplary embodiment, the manufacturing method of the RTB system sintered magnet of the present invention is to manufacture the RTB system sintered magnet (R is a rare earth element and must include at least one selected from Nd, Pr and Ce, T is at least one of the transition metals and must include Fe), and the manufacturing method includes: a process of preparing a coarsely crushed powder of an alloy for RTB system sintered magnet with an average particle size of 10 μm to 500 μm; a process of supplying the above-mentioned coarsely crushed powder to a jet mill device whose crushing chamber is filled with an inert gas and crushing the above-mentioned coarsely crushed powder to obtain a fine powder with an average particle size of 2.0 μm to 4.5 μm; and a process of preparing a sintered body of the above-mentioned fine powder, the above-mentioned inert gas is humidified, and the oxygen content of the above-mentioned RTB system sintered magnet is calculated by mass ratio. 1000 ppm to 3500 ppm.

[0016] In one embodiment, the RTB based sintered magnet has an R content of 31 mass % or less.

[0017] In one embodiment, the inert gas is nitrogen.

[0018] In one embodiment, the method further includes diffusing a heavy rare earth element RH (RH is at least one of Tb, Dy, and Ho) from the surface of the sintered body to the inside.

[0019] In one embodiment, the step of producing a sintered body of the fine powder includes: producing a powder compact from the fine powder by wet pressing in a magnetic field or pressing in a magnetic field in an inert gas atmosphere; and sintering the powder compact.

[0020] In one embodiment, the average particle size of the fine powder in the step of obtaining the fine powder is 2.0 μm or more and 3.5 μm or less.

[0021] In the non-limiting exemplary embodiment of the RTB system sintered magnet of the present invention, R is a rare earth element and must include at least one selected from Nd, Pr and Ce, T is at least one transition metal and must include Fe, and R as the main phase of the RTB system sintered magnet is 2 T 14 The average grain size of phase B is not less than 3 μm and not more than 7 μm, and it contains oxygen, carbon and nitrogen. The oxygen content is not less than 1000 ppm and not more than 3500 ppm in terms of mass ratio, the carbon content is not less than 80 ppm and not more than 1500 ppm in terms of mass ratio, and the nitrogen content is not less than 50 ppm and not more than 600 pm in terms of mass ratio. When the oxygen content in terms of mass ratio is set to [O], the carbon content is set to [C], and the nitrogen content is set to [N], the following formulas 1 to 3 are satisfied.

[0022] Formula 1: [O]>[C]>[N], Formula 2: [O]≥1.5×[N], Formula 3: [C]≥1.5×[N].

[0023] In a non-limiting exemplary embodiment, the RTB based sintered magnet of the present invention comprises R 2 T 14 RTB system sintered magnet having a main phase composed of B compound and a grain boundary phase located in the grain boundary part of the above main phase (R is a rare earth element and must contain at least one selected from Nd, Pr and Ce, T is at least one of the transition metals and must contain Fe), R as the main phase of the above RTB system sintered magnet 2 T 14The average grain size of the B phase is not less than 3 μm and not more than 7 μm. The above-mentioned RTB-based sintered magnet contains oxygen, carbon and nitrogen, and the oxygen content is not less than 1000 ppm and not more than 3500 ppm in terms of mass ratio, and the nitrogen content is not less than 50 ppm and not more than 600 pm in terms of mass ratio. The above-mentioned grain boundary phase has a rare earth oxide phase, and the above-mentioned rare earth oxide phase contains a rare earth nitride phase having a NaCl type crystal structure. When the O content (atomic %) in the above-mentioned rare earth oxide nitride phase is set to {O}, and the N content (atomic %) in the above-mentioned rare earth oxide nitride phase is set to {N}, the relationship of {O}>1.8×{N} is satisfied.

[0024] In one embodiment, the RTB based sintered magnet satisfies the relationship of {C}>{N}×0.5 when the content (atomic %) of C in the rare earth oxynitride phase is {C}.

[0025] In one embodiment, in any cross section of the RTB based sintered magnet, the ratio of the area of ​​the rare earth oxynitride phase to the area of ​​the rare earth oxide phase is 50% or more.

[0026] In one embodiment, the RTB based sintered magnet includes a portion in which at least one of the Tb concentration and the Dy concentration gradually decreases from the magnet surface toward the inside of the magnet.

[0027] Effects of the Invention

[0028] According to the embodiment of the present invention, the particle surface of the fine powder obtained by jet milling can be appropriately modified by using the humidified inert gas. Thus, even if the particle size of the fine powder is reduced, the deterioration of the pulverization efficiency during jet milling can be suppressed, and an RTB-based sintered magnet having excellent magnetic properties can be finally obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 1 is a diagram schematically showing a configuration example of a sintered RTB based magnet alloy pulverizing system 1000 according to the present embodiment. DETAILED DESCRIPTION

[0030] According to the research results of the inventors of the present invention, when manufacturing RTB-based sintered magnets with reduced oxygen content, when the powder particles are reduced in size by the pulverizing process, in addition to the deterioration of the pulverizing efficiency, the powder particles are degraded (nitrided) by the inert gas (especially when dried nitrogen is used as the inert gas) during the pulverizing process, and the desired magnetic property improvement effect caused by the reduction of the pulverized particles cannot be obtained. The inventors of the present invention conducted further research and found that the deterioration of the powder particles caused by the inert gas can be reduced by using a humidified inert gas. It is considered that this is because by forming an oxide film on the surface of the powder particles, the inert gas (especially nitrogen) can be prevented from being introduced into the inside of the powder particles, thereby suppressing the deterioration (nitridation) of the powder particles caused by the inert gas. At present, it is known that when the powder particles are reduced in size by the pulverizing process, the pulverizing efficiency deteriorates, and these deterioration phenomena can be improved by using a humidified inert gas flow (for example, Patent Document 1 and Patent Document 2). However, it is natural that when the humidified inert gas flow is used for pulverization, the powder particles are oxidized and the magnetic properties are reduced. Therefore, in the case of manufacturing an RTB system sintered magnet with a reduced oxygen content in order to improve magnetic properties, there is no active use of a humidified inert gas flow to pulverize in order to reduce the pulverized particles (for example, the oxygen content of the fine powder of Patent Document 1 is relatively high, reaching 4500ppm and 4900ppm by mass ratio, and Patent Document 2 does not record the oxygen content). However, based on the discovery that the deterioration of the powder particles caused by the above-mentioned inert gas can be reduced by using a humidified inert gas, the inventors of the present invention have repeatedly studied and unexpectedly found that in the final RTB system sintered magnet, when the powder particles are humidified and pulverized in a manner to reduce the oxygen content in a specific range, the deterioration (nitridation) of the powder particles can be suppressed, and the reduction in magnetic properties caused by humidified oxidation can be suppressed. In addition, in general, in the process after pulverization, the process of increasing the oxygen content of the RTB system sintered magnet is mainly the process of molding and sintering the fine powder to make a sintered body, but the oxygen content of the RTB system sintered magnet increases less (for example, more than 50ppm and less than 300ppm by mass ratio). Therefore, the oxygen content of the RTB based sintered magnet can be adjusted by the pulverization step.That is, the present invention has found that in the pulverizing process, by performing wet pulverization so that the oxygen content of the obtained RTB system sintered magnet is within a specific range (1000 ppm to 3500 ppm, preferably 1000 ppm to 3200 ppm) to make the powder particles smaller (average particle size is 2.0 μm to 4.5 μm, preferably average particle size is 2.0 μm to 3.5 μm), the pulverizability can be improved, and by reducing the degradation of magnetic properties due to oxidation or nitridation in the pulverizing process, an RTB system sintered magnet with high magnetic properties can be obtained. In this way, the following RTB system sintered magnet can also be appropriately obtained: R as the main phase of the RTB system sintered magnet. 2 T 14 The average grain size of phase B is not less than 3 μm and not more than 7 μm, and it contains oxygen, carbon and nitrogen. The oxygen content is not less than 1000 ppm and not more than 3500 ppm in terms of mass ratio, the carbon content is not less than 80 ppm and not more than 1500 ppm in terms of mass ratio, and the nitrogen content is not less than 50 ppm and not more than 600 pm in terms of mass ratio. When the oxygen content in terms of mass ratio is set to [O], the carbon content is set to [C], and the nitrogen content is set to [N], the following formulas 1 to 3 are satisfied.

[0031] Formula 1: [O]>[C]>[N], Formula 2: [O]≥1.5×[N], Formula 3: [C]≥1.5×[N].

[0032] <Method for producing RTB based sintered magnet>

[0033] Hereinafter, an embodiment of the method for producing an RTB based sintered magnet of the present invention will be described.

[0034] The present invention is a method for producing an RTB-based sintered magnet, wherein R is a rare earth element and must include at least one selected from Nd, Pr and Ce, and T is at least one transition metal and must include Fe.

[0035] The manufacturing method of the RTB-based sintered magnet comprises:

[0036] (1) a step of preparing a coarsely pulverized powder of an alloy for RTB based sintered magnet having an average particle size of 10 μm or more and 500 μm or less;

[0037] (2) supplying the coarsely pulverized powder to a jet mill having a pulverizing chamber filled with an inert gas and pulverizing the coarsely pulverized powder to obtain a fine powder having an average particle size of 2.0 μm to 4.5 μm; and

[0038] (3) a step of preparing a sintered body of the fine powder,

[0039] The inert gas is humidified. The average particle size (d50) can be measured by air flow dispersion laser diffraction method.

[0040] <RTB Sintered Magnet>

[0041] The oxygen content of the RTB system sintered magnet of the present invention is 1000 ppm to 3500 ppm in terms of mass ratio. By making the oxygen content 1000 ppm to 3500 ppm, in the step of obtaining fine powder in the above (2), since the humidification of the inert gas becomes too weak, it is possible to suppress the magnetic properties from being reduced due to the aggravated deterioration (nitridation) of the powder particles caused by the inert gas, or the magnetic properties from being reduced due to the aggravated oxidation of the powder particles caused by the humidification. In order to obtain higher magnetic properties, the oxygen content of the RTB system sintered magnet is preferably 1000 ppm to 3200 ppm, more preferably 1000 ppm to 2400 ppm, and more preferably 1300 ppm to 2400 ppm. In addition, by utilizing humidified pulverization, the RTB sintered magnet is made to have the oxygen content of the present invention (1000 ppm to 3500 ppm), thereby improving the compressibility during molding as shown in the examples described later. By improving the compressibility, molding can be performed at a lower molding pressure. Thus, cracking of the molded body can be suppressed. Furthermore, by reducing the load on the mold, continuous moldability can be improved, and the mold repair frequency can be reduced, thereby improving production efficiency. The oxygen content of the RTB-based sintered magnet is preferably 2000ppm or more. The moldability can be further improved. Therefore, considering the moldability and magnetic properties (B r and H cJ ), the oxygen content of the RTB based sintered magnet is preferably in the range of 2000 ppm to 2400 ppm.

[0042] The following shows the composition of a preferred RTB based sintered magnet.

[0043] R is a rare earth element and must contain at least one selected from Nd, Pr and Ce. Preferably, a combination of rare earth elements represented by Nd-Dy, Nd-Tb, Nd-Dy-Tb, Nd-Pr-Dy, Nd-Pr-Tb, and Nd-Pr-Dy-Tb is used.

[0044] In R, Dy and Tb can play a special role in improving H cJeffect. In addition to the above-mentioned elements, other rare earth elements such as La may also be contained, and cerium alloys or neodymium mixtures may also be used. In addition, R may not be a pure element, and may contain impurities that are inevitable in manufacturing within the range that can be obtained industrially. The content is, for example, 27 mass % to 35 mass %. Preferably, the R content of the RTB system sintered magnet is 31 mass % or less (27 mass % to 31 mass %, preferably 29 mass % to 31 mass %). The R content of the RTB system sintered magnet is 31 mass % or less, and the oxygen content is 1000 ppm to 3500 ppm in terms of mass ratio, thereby reducing the occurrence of R oxidized due to humidification during wet crushing. Therefore, higher magnetic properties can be obtained.

[0045] T contains iron (including the case where T is substantially composed of iron), and 50% or less of it can be replaced by cobalt (Co) in terms of mass ratio (including the case where T is substantially composed of iron and cobalt). Co is effective for improving temperature characteristics and corrosion resistance, and the alloy powder can contain 10% or less of Co. The content of T can account for the balance of R and B, or R and B and M described later.

[0046] The B content may be a known content, and for example, 0.9 mass % to 1.2 mass % is a preferred range. When the content is less than 0.9 mass %, a high H cJ When it exceeds 1.2 mass%, sometimes B r It will decrease. Among them, part of B may be replaced by C (carbon). It is more preferably 1.0 mass % or less, and further preferably 0.96 mass % or less.

[0047] In addition to the above elements, in order to increase H cJ , M element may be added. M element is one or more selected from Al, Si, Ti, V, Cr, Mn, Ni, Cu, Zn, Ga, Zr, Nb, Mo, In, Sn, Hf, Ta and W. The addition amount of M element is preferably 5.0 mass % or less. This is because when it exceeds 5.0 mass %, Br may decrease. In addition, unavoidable impurities are also allowed.

[0048] The N (nitrogen) content in the RTB system sintered magnet is preferably 50 ppm to 600 ppm by mass ratio. By wet crushing in a manner in which the N (nitrogen) content is 50 ppm to 600 ppm by mass ratio, the crushing property can be improved, and the decrease in magnetic properties caused by nitridation can be suppressed. The nitrogen content is further preferably 50 ppm to 400 ppm, and most preferably 100 ppm to 300 ppm. This is to further improve the crushing property and to suppress the decrease in magnetic properties caused by nitridation. In addition, the C (carbon) content in the RTB system sintered magnet is preferably 80 ppm to 1500 ppm by mass ratio, and more preferably 80 ppm to 1000 ppm. In addition, the lower limit of the C content can also be 500 ppm, and can also be 800 ppm or more. In addition, the RTB based sintered magnet of the present invention preferably satisfies the following formulas 1 to 3 when the content of oxygen, carbon, and nitrogen by mass ratio is [O], [C], and [N].

[0049] Formula 1: [O]>[C]>[N], Formula 2: [O]≥1.5×[N], Formula 3: [C]≥1.5×[N].

[0050] By satisfying the above-mentioned formulas 1 to 3, the pulverizability can be improved more reliably, and an RTB-based sintered magnet that takes into account both the suppression of deterioration of powder particles and the suppression of the decrease in magnetic properties caused by humid oxidation can be obtained. The RTB-based sintered magnet of the present invention is pulverized with moisture as described above, and the oxygen content increases, but the nitridation caused by pulverization can be particularly suppressed. As a result, the contents of oxygen, carbon, and nitrogen in the obtained RTB-based sintered magnet can satisfy formula 1 ([O]>[C]>[N]). In addition, by fully suppressing nitridation, the nitrogen content is less than the oxygen and carbon contents, and formula 2 ([O]≥1.5×[N]) and formula 3 ([C]≥1.5×[N]) can be satisfied. In addition, formula 2 is more preferably [O]≥3×[N], more preferably [O]≥5×[N], and most preferably [O]≥10×[N]. In addition, formula 3 is more preferably [C]≥2×[N], and most preferably [C]≥5×[N].

[0051] In addition, R as the main phase of the RTB based sintered magnet of the present invention 2 T 14 The average crystal grain size of the B phase is 3.5 μm or more and 7.0 μm or less. The average crystal grain size can be obtained by averaging the equivalent circle diameters of crystal grains (5000 or more) evaluated by EBSD (Electron Back Scatter Diffraction).

[0052] <(1) Example of a process for preparing a coarsely pulverized powder of an alloy for RTB based sintered magnet having an average particle size of 10 μm or more and 500 μm or less>

[0053] The step of preparing a coarsely pulverized powder of an RTB based sintered magnet alloy having an average particle size of 10 μm to 500 μm includes the steps of preparing the RTB based sintered magnet alloy and coarsely pulverizing the alloy by, for example, hydrogen pulverization.

[0054] The method for producing an alloy for RTB-based sintered magnets is illustrated. The metal or alloy pre-adjusted to the above composition is melted and cast into a mold to obtain an alloy ingot. In addition, the molten metal can be brought into contact with a single roll, double roll, rotating disk or rotating cylinder mold to be rapidly cooled, and a thinner solidified alloy than the alloy obtained by the ingot casting method can be produced by a rapid cooling method represented by a thin strip continuous casting method or a centrifugal casting method, so as to produce an alloy sheet.

[0055] In an embodiment of the present invention, materials manufactured by any method of the ingot casting method and the rapid cooling method can be used, and it is preferably manufactured by a rapid cooling method such as a thin strip continuous casting method. The thickness of the quenched alloy made by the rapid cooling method is usually in the range of 0.03 mm to 1 mm, and is in the shape of a thin sheet. The alloy melt begins to solidify from the contact surface of the cooling roller (roller contact surface), and the crystal grows columnarly from the roller contact surface to the thickness direction. Compared with the alloy (ingot alloy) obtained by the existing ingot casting method (mold casting method), the quenched alloy is cooled in a short time, so the structure is refined and the crystal grain size is small. In addition, the area of ​​the grain boundary is large. The R-rich phase expands widely in the grain boundary, so the dispersibility of the R-rich phase is excellent when using the rapid cooling method. Therefore, it is easy to break at the grain boundary using the hydrogen pulverization method. By hydrogen pulverizing the quenched alloy, the size of the hydrogen pulverized powder (coarse pulverized powder) can be made, for example, less than 1.0 mm. The coarse pulverized powder obtained in this way is pulverized by a jet mill in a humidified atmosphere (step (2)).

[0056] <(2) Example of a process of supplying coarsely pulverized powder to a jet mill having a pulverizing chamber filled with an inert gas and pulverizing the coarsely pulverized powder to obtain a fine powder having an average particle size of 2.0 μm or more and 4.5 μm or less>

[0057] <Crushing system>

[0058] First, refer to Figure 1 A pulverizing system that can be used in the method for producing a sintered RTB based magnet of the present invention will be described. Figure 1 1 is a diagram schematically showing a configuration example of a pulverizing system 1000 according to the present embodiment. In this example, the RTB based sintered magnet alloy pulverizing system 1000 includes a jet mill device 100 , a cyclone collector device 200 , and a bag filter device 300 .

[0059] The jet mill device 100 receives the supply of the material to be crushed from the raw material tank (not shown) via the raw material input pipe 34. The material to be crushed is a coarsely crushed powder of an alloy for RTB-based sintered magnets having an average particle size of 10 μm or more and 500 μm or less. The average particle size (d50) in the present invention can be measured by airflow dispersion laser diffraction method (based on JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size refers to the particle size (median particle size) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.

[0060] The average particle size (d50) in the embodiment of the present invention refers to d50 measured using a particle size distribution measuring apparatus "HELOS & RODOS" manufactured by Sympatec under the conditions of dispersion pressure: 4 bar, measurement range: R2, and calculation mode: HRLD.

[0061] The raw material input pipe 34 is provided with a plurality of valves, and the internal pressure of the jet mill device 100 is appropriately maintained by opening and closing the valves. The material to be pulverized introduced into the jet mill device 100 collides with the impact plate provided to effectively pulverize the material to be pulverized due to the high-speed injection of the inert gas from the nozzle pipe 36, and is finely pulverized. A humidifying pipe for making the inert gas contain water is connected to the nozzle pipe 36.

[0062] The powder of the alloy for RTB-based sintered magnet is active and easily oxidized. Therefore, as the gas used in the jet mill device 100, in order to avoid the danger of heat and fire and reduce the oxygen content as an impurity to achieve high performance of the magnet, dry (high-purity) nitrogen, argon, helium and other inert gases with a dew point below -60°C are usually used. However, in an embodiment of the present invention, pulverization is performed in a humidified state in which moisture is intentionally introduced into such an inert gas. Details on this point will be described later.

[0063] Inside the jet mill device 100, the finely pulverized powder particles (fine powder) are introduced into the inlet pipe 20 of the cyclone collector 200 from the upper discharge port 40 by the rising air flow. The insufficiently pulverized coarse particles are sorted by the classifying rotor provided to classify the coarse particles with a median particle size (d50) or more, and are retained in the jet mill device 100 to further undergo a pulverization process using impact. For the classification of the coarse particles, a classifying rotor can be used, or a centrifugal separation using a rotating airflow can be used. In this way, the pulverized material (coarsely pulverized powder) put into the jet mill device 100 is pulverized into fine powder having a particle size distribution with an average particle size (median particle size: d50) of 2.0 μm or more and 4.5 μm or less, and then moved to the cyclone collector 200.

[0064] The cyclone collector 200 is used to separate powder from the airflow that transports the powder. Specifically, the coarsely pulverized powder of the alloy for RTB-based sintered magnets is pulverized in the jet mill in the front section, and the fine powder generated by the pulverization is supplied to the cyclone collector 200 together with the gas used in the pulverization through the inlet pipe 20. The mixture of the inactive gas (pulverized gas) and the pulverized fine powder forms a high-speed airflow and is sent to the cyclone collector 200. The cyclone collector 200 is used to separate these pulverized gases from the fine powder. The fine powder separated from the pulverized gas is recovered in the powder collector 50 via the discharge port 40. The pulverized gas is supplied to the bag filter device 300 via the outlet pipe 30. Very small microparticles are recovered in the bag filter device 300, and the clean gas is discharged to the outside from the exhaust port 32. In addition, in order to perform such solid-gas separation, a bag filter can be used instead of the cyclone collector 200, but the damage of the filter causes the fine powder to be scattered into the atmosphere, which has a great impact on the environment and safety. A bag filter may be used in combination to separate fine particles from the gas separated by the cyclone collector 200 .

[0065] The characteristic point of the present invention is that the oxygen content of the RTB system sintered magnet is wet-pulverized in a manner such that it is within the range of 1000 ppm to 3500 ppm by mass. In this way, both the deterioration (nitridation) of the powder particles caused by the pulverization and the oxidation caused by the humidification can be suppressed, and high magnetic properties can be obtained. As mentioned above, the increase in the oxygen content of the RTB system sintered magnet caused by the subsequent steps of the pulverization (mainly the step of making the sintered body of the above-mentioned fine powder) is usually small (for example, 50 ppm to 300 ppm). Therefore, the oxygen content of the RTB system sintered magnet can be adjusted by the pulverization step.

[0066] Specifically, the humidified inert gas in step (2) can be obtained, for example, by adding water to the inert gas in an amount of 0.5 g to 6.0 g per 1 kg of the coarsely pulverized powder. When the amount is less than 0.5 g, the deterioration (nitridation) of the powder particles caused by the pulverization cannot be suppressed, and the magnetic properties may be reduced. On the other hand, when the amount exceeds 6.0 g, excessive humidification may occur, and thus oxidation of the powder particles may be aggravated, and the magnetic properties may be reduced.

[0067] The dew point in the pulverizing chamber and the amount of the coarsely pulverized powder supplied to the jet mill also depend on the pulverizing time and the size of the jet mill, but in a preferred embodiment, the inert gas is humidified to a dew point of -55°C or more and -30°C or less during pulverization. In a further preferred embodiment, the rate of supplying the coarsely pulverized powder to the jet mill is 35 kg / hour or more and 180 kg / hour or less.

[0068] Examples of inert gases are nitrogen, argon, and helium. Among them, nitrogen is the most preferred gas because it can be obtained at a low cost and with high purity. Therefore, in a preferred embodiment, the inert gas is nitrogen. However, according to the research results of the inventors of the present invention, when the average particle size of the obtained fine powder is less than 4.5 μm using the existing method and using an inert gas containing nitrogen, the magnetic properties begin to decrease due to nitridation. In particular, it is known that when the average particle size is less than 3.5 μm, the decrease in magnetic properties caused by nitridation sometimes becomes significant. However, using an embodiment of the present invention, since the pulverization is carried out under a properly adjusted humidified atmosphere, even if nitrogen is used as the inert gas, it is possible to take into account both the inhibition of nitridation and the inhibition of oxidation. It is considered that this is because even if the inert gas in the pulverizing chamber is mainly nitrogen, by humidifying it to contain a specific adjusted amount of moisture, the active surface of the particles expressed by the fine pulverization can be slightly oxidized before being nitrided. Among them, the increase in oxygen content of the RTB-based sintered magnet caused by the process after fine pulverization (mainly the process of making the sintered body of the above-mentioned fine powder) is preferably 50 ppm to 300 ppm in terms of mass ratio, and more preferably 50 ppm to 200 ppm. In order to achieve such an increase, wet pressing in a magnetic field or pressing in a magnetic field in an inert gas atmosphere is performed as described later, and the obtained molded body is sintered. The average particle size of the fine powder in the process of obtaining the fine powder is 2.0 μm to 4.5 μm. When it is less than 2.0 μm, there is a possibility that the crushing particle size of the fine powder is too small to suppress the deterioration of the crushing efficiency during jet mill crushing; when it exceeds 4.5 μm, there is a possibility that high magnetic properties cannot be obtained. The crushing particle size of the fine powder is more preferably 2.0 μm to 3.5 m. By reducing the average particle size, the magnet properties can be improved.

[0069] <(3) Example of process for producing a sintered body of fine powder>

[0070] In a preferred embodiment, the process of making a sintered body of fine powder includes the process of making a powder molded body from the fine powder by pressing in a magnetic field and the process of sintering the powder molded body. When pressing in a magnetic field, from the viewpoint of oxidation inhibition, it is preferred to form the powder molded body by pressing in an inert gas atmosphere or wet pressing. In particular, in wet pressing, the surface of the particles constituting the powder molded body is covered with a dispersant such as an oil agent, which inhibits contact with oxygen or water vapor in the atmosphere. Therefore, it is possible to prevent or inhibit the particles from being oxidized by the atmosphere before or after the pressing process or during the pressing process.

[0071] When wet pressing in a magnetic field is performed, a slurry in which a dispersion medium is mixed with fine powder is prepared, supplied to a cavity in a mold of a wet pressing device, and press molding is performed in a magnetic field.

[0072] Dispersion medium

[0073] The dispersion medium is a liquid in which the alloy powder can be dispersed to obtain a slurry.

[0074] As the preferred dispersion medium used in the present invention, mineral oil or synthetic oil can be cited. The type of mineral oil or synthetic oil is not specific, but when the kinematic viscosity at room temperature exceeds 10 cSt, the bonding force between the alloy powders is enhanced due to the increased viscosity, which sometimes has an adverse effect on the orientation of the alloy powder during wet molding in a magnetic field. Therefore, the kinematic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. In addition, when the fractionation temperature of the mineral oil or synthetic oil exceeds 400°C, degreasing after obtaining the molded body becomes difficult, and sometimes the amount of residual carbon in the sintered body increases, and the magnetic properties decrease. Therefore, the fractionation temperature of the mineral oil or synthetic oil is preferably 400°C or less. In addition, vegetable oil can also be used as a dispersion medium. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.

[0075] ·Slurry preparation

[0076] The obtained alloy powder is mixed with a dispersion medium to obtain a slurry.

[0077] The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more). 3 At a flow rate of 1000 g / min / s, alloy powder can be efficiently supplied to the inside of the mold cavity, and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less in terms of mass ratio. The method for mixing the alloy powder and the dispersion medium is not particularly limited. The alloy powder and the dispersion medium can be prepared separately, and the two can be weighed in a specified amount and mixed to produce. In addition, when the coarsely pulverized powder is dry-pulverized by a jet mill or the like to obtain the alloy powder, a container containing a dispersion medium can be arranged at the alloy powder discharge port of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization is directly recovered in the dispersion medium in the container to obtain a slurry. In this case, it is preferred that an atmosphere formed by nitrogen and / or argon is also formed in the container, so that the obtained alloy powder is not in contact with the atmosphere and is directly recovered in the dispersion medium to form a slurry. In addition, a vibration mill, a ball mill or a grinding mill, etc., is used to wet-pulverize the coarsely pulverized powder in a state maintained in the dispersion medium, and a slurry consisting of an alloy powder and a dispersion medium can also be obtained.

[0078] The slurry thus obtained is molded using a known wet press to obtain a molded body having a predetermined size and shape. The molded body is chemically sintered to obtain a sintered body.

[0079] Sintering process

[0080] Next, the molded body is sintered to obtain a rare earth sintered magnet body (sintered body).

[0081] The sintering of the molded body is preferably carried out at 0.13 Pa (10 -3 Torr) or less, more preferably 0.07 Pa (5.0×10 -4 Torr) and at a temperature range of 1000°C to 1150°C. In order to prevent oxidation caused by sintering, the residual gas in the atmosphere can be replaced with an inactive gas such as helium or argon. The obtained sintered body is preferably heat-treated. The magnetic properties can be improved by heat treatment. The heat treatment conditions such as heat treatment temperature and heat treatment time can adopt known conditions. For the rare earth sintered magnet obtained in this way, a grinding / polishing process, a surface treatment process and a magnetization process are carried out as needed to complete the final rare earth sintered magnet.

[0082] In a preferred embodiment, the method for producing an RTB-based sintered magnet of the present invention further includes a diffusion step of diffusing a heavy rare earth element RH (RH is at least one of Tb, Dy, and Ho) from the surface of the sintered body to the inside. When the heavy rare earth element RH is diffused from the surface of the sintered body to the inside, the coercive force can be effectively improved. As shown in the embodiments described below, when the diffusion step is performed on the sintered body of the present invention that has been subjected to wet pulverization, a high H can be obtained compared to the case where the diffusion step is performed on the sintered body that has not been subjected to wet pulverization. cJ . The method of the diffusion process is not particularly limited. A known method can be used. As the heavy rare earth element RH, Tb and Dy are preferred. The RTB system sintered magnet obtained by diffusing them contains a portion in which at least one of the Tb concentration and the Dy concentration decreases from the magnet surface to the inside of the magnet. That is, the RTB system sintered magnet contains a portion in which at least one of the Tb concentration and the Dy concentration decreases from the magnet surface to the inside of the magnet, which means that at least one of Tb and Dy is diffused from the magnet surface to the inside of the magnet. This state can be confirmed, for example, by performing a linear analysis (line analysis) on an arbitrary cross-section of the RTB system sintered magnet from the magnet surface to near the center of the magnet using an energy dispersive X-ray spectroscopy method (EDX).

[0083] When the size of the measurement site is, for example, submicron, the concentrations of Tb and Dy can be determined by the location of the measurement site in the main phase grain (R 2 T 14B compound particles) and grain boundaries. In addition, when the measurement site is located at the grain boundary, the concentration of Tb or Dy may change locally or microscopically depending on the type and distribution of compounds containing Tb or Dy that can be formed at the grain boundary. However, when it is clear that Tb and Dy diffuse from the surface of the magnet to the inside of the magnet, the average concentration of these elements at positions with equal depth from the surface of the magnet gradually decreases from the surface of the magnet to the inside of the magnet. In the present invention, in an area from the magnet surface to a depth of 200μm of at least the RTB system sintered magnet, when at least one of the average concentrations of Tb and Dy measured by a function with depth as a parameter decreases with increasing depth, the RTB system sintered magnet is defined as a portion containing at least one of a decreasing Tb concentration and a decreasing Dy concentration.

[0084] The R content of the RTB system sintered magnet finally obtained after the diffusion process of diffusing the heavy rare earth element RH from the surface to the inside of the sintered body is preferably 32 mass % or less (27 mass % or more and 32 mass % or less). By making the R content of the RTB system sintered magnet 32 ​​mass % or less and the oxygen content in mass ratio of 1000 ppm or more and 3500 ppm or less (preferably 1000 ppm or more and 3200 ppm or less, more preferably 1000 ppm or more and 2400 ppm or less, more preferably 2000 ppm or more and 2400 ppm or less), higher magnetic properties can be obtained.

[0085] The N (nitrogen) content in the RTB system sintered magnet finally obtained after the diffusion process is preferably 50 ppm to 600 ppm in terms of mass ratio, more preferably 50 ppm to 400 ppm, and most preferably 100 ppm to 300 ppm. In addition, the C (carbon) content in the RTB system sintered magnet is preferably 80 ppm to 1500 ppm in terms of mass ratio, and more preferably 80 ppm to 1000 ppm. In addition, when the oxygen content in the RTB system sintered magnet finally obtained after the diffusion process is set to [O], the carbon content is set to [C], and the nitrogen content is set to [N], it is preferred to satisfy the following formulas 1 to 3.

[0086] Formula 1: [O]>[C]>[N], Formula 2: [O]≥1.5×[N], Formula 3: [C]≥1.5×[N].

[0087] In addition, the inventors of the present invention conducted a detailed investigation on the structure of the RTB-based sintered magnet obtained by wet pulverization of the present invention, and found that the grain boundary phase of the RTB-based sintered magnet has a rare earth oxide phase, and the rare earth oxide phase has a rare earth oxynitride phase. It was also found that high magnetic properties can be obtained by having the rare earth oxynitride phase have a specific crystal structure and the contents (atomic %) of oxygen {O} and nitrogen {N} satisfying a specific relationship. It can also be seen that the effect is particularly significant when the diffusion process of diffusing the heavy rare earth element RH from the surface to the inside of the sintered body is performed (the H generated by the diffusion is cJ Such a structure can be suitably obtained by wet grinding of the present invention, but is not necessarily limited thereto. For example, by adjusting the amount of oxygen and nitrogen introduced into the jet mill grinding, the RTB system sintered magnet described below can be obtained.

[0088] The RTB sintered magnet of the present invention comprises R 2 T 14 RTB system sintered magnet having a main phase composed of B compound and a grain boundary phase located in the grain boundary part of the above main phase (R is a rare earth element and must contain at least one selected from Nd, Pr and Ce, T is at least one of the transition metals and must contain Fe), R as the main phase of the above RTB system sintered magnet 2 T 14 The average crystal grain size of the B phase is 3 μm or more and 7 μm or less, the RTB system sintered magnet contains oxygen, carbon and nitrogen, the oxygen content is 1000 ppm or more and 3500 ppm or less by mass ratio, and the nitrogen content is 50 ppm or more and 600 ppm or less by mass ratio, the grain boundary phase has a rare earth oxide phase, the rare earth oxide phase includes a rare earth oxynitride phase having a NaCl type crystal structure, and when the content (atomic %) of O in the rare earth oxynitride phase is {O}, and the content (atomic %) of N in the rare earth oxynitride phase is {N}, the relationship of {O}>1.8×{N} is satisfied. Preferably, when the content (atomic %) of C in the rare earth oxynitride phase is {C}, the RTB system sintered magnet further satisfies the relationship of {C}>{N}×0.5.

[0089] The ratio of the area of ​​the rare earth oxynitride phase to the area of ​​the rare earth oxide phase is preferably 50% or more.

[0090] R as the main phase of RTB based sintered magnet 2 T 14The average crystal grain size of the B phase is 3 μm to 7 μm (preferably 3 μm to 5 μm), and the RTB system sintered magnet contains oxygen, carbon, and nitrogen, and the oxygen content is 1000 ppm to 3500 ppm (preferably 1000 ppm to 2500 ppm), and the nitrogen content is 50 ppm to 600 pm. Thus, high magnetic properties can be obtained. In addition, the grain boundary phase of the RTB system sintered magnet has a rare earth oxide phase, and the rare earth oxide phase includes a rare earth oxynitride phase having a NaCl type crystal structure. According to the research results of the inventors of the present invention, it can be seen that the rare earth oxynitride phase having a NaCl type crystal structure is easy to combine with carbon (C). Therefore, it can be seen that by including a rare earth oxynitride phase having a NaCl type crystal structure, the C amount of the main phase can be reduced, thereby obtaining high magnetic properties. It can also be seen that the rare earth oxynitride phase having a NaCl type crystal structure is not easy to form oxides with heavy rare earth elements (such as Tb and Dy). Therefore, when the RTB system sintered magnet contains Tb and Dy, by including a rare earth oxynitride phase having a NaCl type crystal structure at the grain boundary, more Tb and Dy can be contained in the main phase, and high magnetic properties can be obtained. As shown in the embodiments described below, the effect is particularly significant when a diffusion process is performed to diffuse the heavy rare earth element RH from the surface to the inside of the sintered body. In addition, the above-mentioned rare earth oxynitride phase satisfies the relationship of {O}>1.8×{N} when the content (atomic %) of O in the above-mentioned rare earth oxynitride phase is set to {O} and the content (atomic %) of N in the above-mentioned rare earth oxynitride phase is set to {N}. By satisfying such a relationship, nitridation of the RTB system sintered magnet can be suppressed and high magnetic properties can be obtained. In addition, the NaCl type rare earth oxynitride forms a nitride with the heavy rare earth element. Therefore, when the RTB system sintered magnet contains Tb and Dy, the contents of O and N in the rare earth oxynitride phase having a NaCl type crystal structure in the grain boundary satisfy the relationship of {O}>1.8×{N}, which can suppress the formation of nitrides with heavy rare earth elements, allowing more Tb and Dy to be contained in the main phase, thereby obtaining high magnetic properties. As shown in the examples described later, the effect is particularly significant when a diffusion process is performed to diffuse the heavy rare earth element RH from the surface to the inside of the sintered body.

[0091] Furthermore, when the C content (atomic %) in the rare earth oxynitride phase is preferably {C}, the relationship of {C}>{N}×0.5 is preferably satisfied, thereby reducing the C content of the main phase and obtaining higher magnetic properties.

[0092] In addition, the area ratio of the rare earth oxynitride phase to the area ratio of the rare earth oxide phase is preferably 50% or more. The magnetic properties can be further improved by making the area ratio of the rare earth oxynitride phase to the rare earth oxide phase 50% or more. Preferably, the area ratio of the rare earth oxynitride phase to the area ratio of the rare earth oxide phase is 70% or more, and more preferably 90% or more.

[0093] "Whether the grain boundary phase of the RTB system sintered magnet has a rare earth oxide phase, and whether the above rare earth oxide phase contains a rare earth oxynitride phase having a NaCl type crystal structure" can be confirmed, for example, by observing the diffraction peaks or patterns unique to the NaCl type crystal structure using diffraction measurements such as X-rays, neutrons, and electron beams.

[0094] "Whether the above-mentioned rare earth oxynitride phase satisfies the relationship of {O}>1.8×{N} when the content of O (atomic %) in the above-mentioned rare earth oxynitride phase is set to {O}, and the content of N (atomic %) in the above-mentioned rare earth oxynitride phase is set to {N}" can be confirmed, for example, by performing point, line or surface analysis of the oxide phase using EDX (energy dispersive X-ray analysis) or WDX (wavelength dispersive X-ray analysis).

[0095] "Whether the proportion of the area of ​​the above-mentioned rare earth oxynitride phase to the area of ​​the above-mentioned rare earth oxide phase is greater than 50%" can be confirmed, for example, as follows: EDX or WDX mapping is performed in a certain field of view, and the above-mentioned rare earth oxide phases are distinguished by color using commercially available software, and then the above-mentioned rare earth oxynitride phases are distinguished by color, and the number of pixels of the color of each phase is counted.

[0096] Example

[0097] The present invention will be described in more detail using examples, but the present invention is not limited to these examples.

[0098] Example 1

[0099] Alloys for RTB sintered magnets are produced by a thin strip continuous casting method in a manner that roughly corresponds to the composition of the RTB sintered magnets shown in Samples No. 1 to 13 in Table 1 (excluding O, C, and N). Each alloy obtained is coarsely pulverized by a hydrogen pulverization method to obtain a coarsely pulverized powder. The average particle size of the coarsely pulverized powder is measured. The average particle size is in the range of 200 μm to 400 μm. In the present invention, the average particle size refers to the particle size (median particle size) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%. The average particle size (d50) is measured using a particle size distribution measuring device "HELOS & RODOS" manufactured by Sympatec under the conditions of dispersion pressure: 4 bar, measurement range: R2, and calculation mode: HRLD.

[0100] The coarsely pulverized powder is added Figure 1 In the jet mill device 100, the coarsely crushed powder is crushed to obtain fine powder. The crushing conditions are shown in Table 2. Regarding No. 2 in Table 2, the inert gas is given 1.5 g of water per 1 kg of coarsely crushed powder and then wet crushed, and the amount of coarsely crushed powder supplied to the jet mill device is 64.0 kg / h. No. 1 and No. 3 to 13 are all described in the same way (No. 1 is crushed without humidification). Among them, in this embodiment, nitrogen is used as the inert gas. The average particle size of the obtained fine powder is shown in Table 2. The above-mentioned fine powder is immersed in a mineral oil with a fractionation temperature of 250°C and a kinematic viscosity of 2 cSt at room temperature in a nitrogen atmosphere to prepare a slurry. The slurry concentration is 85% by mass. The obtained slurry is molded in a magnetic field (wet molding) to obtain a molded body. Among them, the molding device uses a so-called right-angle magnetic field molding device (transverse magnetic field molding device) in which the direction of magnetic field application is orthogonal to the direction of pressure application. The obtained molded body was sintered in vacuum at 1040°C (a temperature selected to achieve sufficient densification by sintering) for 4 hours to obtain a sintered body. The density of the sintered body was 7.5 Mg / m 3 The above. Then, the sintered body was kept at 800°C for 2 hours, cooled to room temperature, and then kept at 500°C for 2 hours, and then subjected to heat treatment to cool to room temperature to obtain a sintered body (RTB system sintered magnet). The composition of the obtained sintered magnet was determined. The contents of Nd, Pr, B, Co, Al, Cu, Ga, and Zr were determined by ICP emission spectrometry. Then, O (oxygen content) was determined using a gas analyzer using a gas melting-infrared absorption method, N (nitrogen content) was determined using a gas analyzer using a gas melting-thermal conduction method, and C (carbon content) was determined using a gas analyzer using a combustion-infrared absorption method. Among them, the contents of O, C, and N are mass ppm. The results are shown in Table 1. The sintered magnet was machined to produce samples with a length of 7 mm, a width of 7 mm, and a thickness of 7 mm. The BH tracer was used to measure the B content of each sample. r and H cJ The measurement results are shown in Table 3. As shown in Table 1, the examples of the present invention all satisfy the formulas 1 to 3 of the present invention. In addition, for each sample, the average crystal grain size (the average value of the equivalent circle diameter of the crystal grains obtained by evaluating about 5700 to 5800 particles) was measured by EBSD, and it was between 4.1 and 4.3 μm.

[0101] [Table 1]

[0102] (quality%)

[0103]

[0104] (C, O, N in ppm)

[0105] [Table 2]

[0106]

[0107] [Table 3]

[0108]

[0109] As shown in Tables 1 and 2, except for C, O, and N, No. 1 to 5 have basically the same composition, and the average particle size of the fine powder obtained by jet milling is also basically the same. As shown in Table 3, the examples of the present invention (No. 2 to 4) have obtained high magnetic properties compared with No. 1 without wet milling. It is currently believed that if the composition and particle size are basically the same, the magnetic properties will decrease when the oxygen content increases. However, as shown in No. 1 and No. 2 to 4, if the oxygen content of the RTB system sintered magnet of the present invention is within the range, the magnetic properties are improved (H cJ Improved). In addition, even if wet pulverization is performed, when the oxygen content of the RTB system sintered magnet of the present invention deviates from the range, the magnetic properties are reduced as shown in No. 5. In addition, when pulverized to an average particle size of about 3.3 μm as shown in Table 2, the present invention example can increase the supply speed compared to the comparative example (No. 1) without humidification, that is, the pulverization property is good. In addition, according to the results of Tables 2 and 3, in order to obtain higher pulverization property, the oxygen content of the RTB system sintered magnet is preferably 1700 ppm or more. In addition, as shown in Table 3, the present invention examples all obtained B r ≥1.33T and H cJ High magnetic properties ≥1200kA / m.

[0110] Example 2

[0111] Sintered bodies No. 1 to 3 of Example 1 are prepared. For the above-mentioned sintered bodies, a diffusion process of diffusing the heavy rare earth element RH from the surface to the inside of the sintered bodies is performed. Specifically, the raw materials of each element are weighed in such a way that the composition becomes Pr80Tb10Ga7Cu3 in terms of mass ratio, and these raw materials are melted to obtain a strip or flake alloy by a single-roll ultra-quenching method (melt spinning method). After the obtained alloy is crushed in an argon atmosphere, it is passed through a sieve with a mesh of 425μm to prepare a diffusion alloy powder. The sintered bodies No. 1 to 3 of Table 1 are cut and ground into cubes of 7.2mm×7.2mm×7.2mm. Next, 2.5% by mass of the above-mentioned diffusion alloy relative to 100% by mass of the RTB-based sintered magnet is scattered on the entire surface of the sintered bodies of No. 1 to 3. After that, the mixture was heat treated at 900°C for 10 hours in a reduced pressure argon atmosphere controlled at 50 Pa, cooled to room temperature, and then heat treated at 500°C for 3 hours in a reduced pressure argon atmosphere controlled at 50 Pa to produce diffused RTB sintered magnets (No. 20 to 23).

[0112] The magnetic properties of the RTB based sintered magnet obtained after the diffusion process were measured in the same manner as in Example 1. The results are shown in Table 4. cJ The improvement value is shown in Table 4. cJ No.6 in Table 4 is the H after diffusion cJ The value of (1826 kA / m) minus the H of magnet No. 1 before diffusion cJ The value obtained by using the energy dispersive X-ray spectroscopy (EDX) method is the same as that of 1139 kA / m. The other values ​​are recorded in the same way. Among them, after linear analysis (line analysis) of the cross section of the RTB-based sintered magnet from the magnet surface to the vicinity of the center of the magnet, it was confirmed that there was a portion where the Tb concentration decreased from the magnet surface to the inside of the magnet.

[0113] [Table 4]

[0114]

[0115] As shown in Table 4, the examples of the present invention (No. 21 and No. 22) in which the sintered body subjected to the wet pulverization of the present invention was subjected to the diffusion step obtained a higher ΔH than the comparative example (No. 20) in which the sintered body was subjected to the diffusion step without the wet pulverization. cJ .

[0116] The moldability of the fine powders prepared under the conditions of No. 1 to 4 and No. 6 and 7 in Table 1 was confirmed. The results are shown in Table 5. The molding pressure shown in Table 5 is the pressure at which the density of the molded body reaches 4.1 g / cm 3 (ρg=4.1g / cm 3Therefore, the lower the molding pressure, the better the compressibility and the better the moldability.

[0117] [Table 5]

[0118]

[0119] As shown in Table 5, compared with the comparative examples, the examples of the present invention have lower molding pressures and better compressibility. 2 In particular, when the molding pressure of No. 4 to 7 was less than half of that of the comparative example, the compressibility was greatly improved, and it was possible to mold at 0.15 kgf / cm 2 Therefore, the oxygen content of the RTB based sintered magnet is preferably 2000 ppm or more by mass ratio, and the magnetic properties (B r and H cJ ), the oxygen content of the RTB based sintered magnet is preferably in a range of 2000 ppm to 2400 ppm by mass.

[0120] Example 3

[0121] The same operation as in Example 1 is performed to prepare an alloy for RTB-based sintered magnets in a manner to obtain the composition of the RTB-based sintered magnets shown in Samples No. 23 to 26 in Table 6. The same operation as in Example 1 is performed to coarsely pulverize the obtained alloy for RTB-based sintered magnets to obtain a coarsely pulverized powder. The same operation as in Example 1 is performed to pulverize the obtained coarsely pulverized powder to obtain a fine powder. The pulverizing conditions are shown in Table 7. The same operation as in Example 1 is performed to mold, sinter, and heat-treat the obtained fine powder to obtain an RTB-based sintered magnet. The same operation as in Example 1 is performed to determine the composition of the obtained sintered magnet. Among them, the contents of O, C, and N are mass ppm. The results are shown in Table 6. As shown in Table 6, except for O, C, and N, Samples No. 23 and 24 have basically the same composition. Similarly, except for O, C, and N, Samples No. 25 and 26 have basically the same composition.

[0122] The results of measuring the magnetic properties of the obtained RTB based sintered magnets are shown in Table 8. r H cJ ” is B at room temperature (23℃) r and H cJ The value of "140℃H cJ ” is H at 140℃ cJ The RTB based sintered magnet after heat treatment was machined to a size of 7 mm × 7 mm × 7 mm and the BH tracer was used to measure the B r , HcJ In addition, calculate the temperature coefficient (β: 23 to 140°C) by the following operation. cj Set to H cj140 , and the H at 23℃ cj Set to H cj23 When the temperature coefficient = (H cj140 -H cj23 ) / H cj23 / (140°C-23°C)×100%, indicating that the smaller the absolute value of the temperature coefficient is, the more the temperature coefficient is improved.

[0123] As shown in Table 8, the present invention example obtained a B of 1.391T or more. r 、H above 1190KA / m cj and β of less than -0.578, and comparing No. 23, 24 or No. 25, 26 having substantially the same composition, the examples of the present invention all have improved temperature coefficients.

[0124] [Table 6]

[0125] (quality%)

[0126]

[0127] [Table 7]

[0128]

[0129] [Table 8]

[0130]

[0131] Example 4

[0132] The same operation as in Example 1 is performed to produce an alloy for RTB-based sintered magnets in a manner to obtain the composition of the RTB-based sintered magnets shown in Sample No. 27 and 28 in Table 9. The same operation as in Example 1 is performed to coarsely grind the obtained alloy for RTB-based sintered magnets to obtain coarsely ground powder. The same operation as in Example 1 is performed to grind the obtained coarsely ground powder to obtain fine powder. The grinding conditions are shown in Table 10. The same operation as in Example 1 is performed to mold, sinter, and heat-treat the obtained fine powder to obtain an RTB-based sintered magnet. The same operation as in Example 1 is performed to determine the composition of the obtained sintered magnet. The results are shown in Table 9.

[0133] As shown in Table 9, samples No. 27 and 28 have basically the same composition except for O, C, and N. The contents of O, C, and N are expressed in mass ppm. In addition, the results of measuring the magnetic properties of the obtained RTB based sintered magnets are shown in Table 11. As shown in Table 11, when comparing No. 27 and 28 having basically the same composition, the example of the present invention (No. 28) has high magnetic properties.

[0134] [Table 9]

[0135] (quality%)

[0136]

[0137] [Table 10]

[0138]

[0139] [Table 11]

[0140]

[0141] The grain boundary phases of the RTB based sintered magnets Nos. 27 and 28 were observed.

[0142] Specifically, first, the crystal structure of the oxide phase is identified by electron beam diffraction. As a result, it can be seen that the crystal structures of No. 27 and 28 both have NaCl-type oxide phases. Next, point analysis and mapping using EDX and WDX are performed. For Fe and Nd, EDX, Pr, C, N and O are analyzed using WDX. Regarding the oxide phase, 3 points are point analyzed for each, and the average value is shown in Table 12. Regarding (A) of Table 12, when the content of O (atomic %) in the rare earth oxynitride phase is set to {O}, and the content of N (atomic %) in the rare earth oxynitride phase is set to {N}, the situation that satisfies the relationship of {O}>1.8×{N} is recorded as "○ circle", and the situation that does not satisfy it is recorded as "×". Similarly, regarding (B), the situation that satisfies {C}>{N}×0.5 is recorded as "○", and the situation that does not satisfy it is recorded as "×".

[0143] In addition, based on the mapping results, the proportion of the rare earth oxynitride phase of the present invention is calculated. First, the mapping intensity of each element is converted into concentration according to the point analysis results using the software "NMap" manufactured by JEOL Ltd. Next, a scatter plot analysis is performed using the software "Phase Map Maker" manufactured by JEOL Ltd. Specifically, the area where {O} ≥ 10 atomic % is distinguished as the area of ​​the oxide phase according to color, and then the areas satisfying formulas (A) and (B) are distinguished according to color, thereby separating the rare earth oxynitride phase of the present invention from other oxide phases. Then, by counting the number of pixels of each color of the obtained image, the cross-sectional area of ​​the rare earth oxynitride phase of the present invention in the rare earth oxide phase is calculated.

[0144] As shown in Table 12, for the example of the present invention (No. 28), the area ratio of the rare earth oxynitride phase of the present invention to the area ratio of the rare earth oxide phase is 70%, and (A) and (B) are satisfied. On the other hand, for the comparative example, the area ratio of the rare earth oxynitride phase of the present invention is 14%, and (A) and (B) are not satisfied.

[0145] [Table 12]

[0146]

[0147] Example 5

[0148] For the sintered bodies of samples No. 27 and 28, a diffusion process of diffusing the heavy rare earth element RH from the surface to the inside of the sintered bodies was further performed. Specifically, the raw materials of each element were weighed in such a way that the composition became Nd31Pr50Tb9Ga5Cu5 in terms of mass ratio, and these raw materials were melted to prepare diffusion alloy powder by an atomization method. The sintered bodies of No. 27 and 28 in Table 1 were cut and ground into rectangular bodies of 7.2 mm × 7.2 mm × 4.7 mm (the direction of 4.7 mm is the direction of magnetic field application during molding). Next, the above-mentioned diffusion alloy was scattered on one surface (7.2 mm × 7.2 mm surface) of the sintered bodies of No. 27 and 28 in an amount of 2 mass % relative to 100 mass % of the RTB-based sintered magnet. After that, the diffused RTB system sintered magnets (No. 29 and 30) were manufactured by heat treatment at 920°C for 10 hours in a reduced pressure argon gas controlled at 50 Pa, cooling to room temperature, and then heat treatment at 450°C for 3 hours in a reduced pressure argon gas controlled at 50 Pa. In addition, the diffused RTB system sintered magnets were confirmed to contain a portion where the Tb concentration gradually decreased from the magnet surface to the inside of the magnet by the same operation as in Example 2.

[0149] The magnetic properties of the RTB based sintered magnets (Nos. 29 and 30) obtained after the diffusion process were measured in the same manner as in Example 1. The results are shown in Table 13. cJ The improvement value is shown in Table 13. cJ .

[0150] [Table 13]

[0151]

[0152] As shown in Table 13, the present invention example (No. 30) that performed the diffusion process obtained a higher ΔH than the comparative example (No. 29). cJ In addition, the same operation as in Example 4 was performed to observe whether the grain boundary phase of the RTB system sintered magnet after diffusion contained the rare earth oxynitride phase of the present invention, and it was confirmed that the composition and the area ratio of the NaCl type rare earth oxynitride phase were basically the same as those in Table 12 (RTB system sintered magnet before diffusion).

[0153] Industrial Applicability

[0154] The method for producing an RTB-based sintered magnet of the present invention can be used for permanent magnets used in a variety of applications such as voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV), motors for industrial equipment, and various other motors and home appliances.

[0155] Explanation of symbols

[0156] 100: jet mill device; 200: cyclone collector device; 300: bag filter device.

Claims

1. A method for producing an R-T-B system sintered magnet, characterized in that: In the R-T-B system sintered magnet, R is a rare earth element and must include at least one selected from Nd, Pr and Ce, T is at least one transition metal and must include Fe, and the manufacturing method comprises: A step of preparing a coarsely pulverized powder of an R-T-B alloy for sintered magnets having an average particle size of 10 μm or more and 500 μm or less; The step of supplying the coarsely pulverized powder to a jet mill device having a pulverizing chamber filled with an inert gas and pulverizing the coarsely pulverized powder to obtain a fine powder having an average particle size of 2.0 μm to 4.5 μm; and a step of preparing a sintered body of the fine powder, The average particle size is the particle size at which the volume-based cumulative particle size distribution from the small particle size side is 50%. The humidified inert gas is obtained by adding 0.5 g or more and 6.0 g or less of water per 1 kg of the coarsely pulverized powder to the inert gas. The oxygen content of the R—T—B based sintered magnet is 1000 ppm or more and 3500 ppm or less in terms of mass ratio.

2. The method for producing an R-T-B system sintered magnet according to claim 1, wherein: The R-T-B based sintered magnet has an R content of 31 mass % or less.

3. The method for producing an R-T-B system sintered magnet according to claim 1 or 2, characterized in that: The inactive gas is nitrogen.

4. The method for producing an R-T-B system sintered magnet according to claim 1 or 2, characterized in that: The method further includes a diffusion step of diffusing a heavy rare earth element RH from the surface to the inside of the sintered body, wherein RH is at least one of Tb, Dy, and Ho.

5. The method for producing an R-T-B system sintered magnet according to claim 1 or 2, characterized in that: The process of making the sintered body of the fine powder includes: A step of making a powder compact from the fine powder by wet pressing in a magnetic field or pressing in a magnetic field in an inert gas atmosphere; and A step of sintering the powder compact.

6. The method for producing an R-T-B system sintered magnet according to claim 1 or 2, characterized in that: The average particle size of the fine powder in the step of obtaining the fine powder is 2.0 μm or more and 3.5 μm or less.

7. An R-T-B system sintered magnet, characterized in that: R is a rare earth element and must contain at least one selected from Nd, Pr and Ce, T is at least one transition metal and must contain Fe, The R2T as the main phase of the R-T-B system sintered magnet 14 The average crystal grain size of the B phase is 3 μm or more and 7 μm or less. The average crystal grain size is the number average of equivalent circle diameters of 5,000 or more crystal grains evaluated by backscattered electron diffraction. A rare earth oxide phase is present in the grain boundary phase located in the grain boundary portion of the main phase, The rare earth oxide phase includes a rare earth oxynitride phase having a NaCl type crystal structure, The R-T-B system sintered magnet also contains oxygen, carbon and nitrogen. The oxygen content is 1000 ppm or more and 3500 ppm or less by mass ratio. The carbon content is 80 ppm or more and 1500 ppm or less by mass ratio. The nitrogen content is 50 ppm or more and 600 ppm or less by mass ratio. When the oxygen content in terms of mass ratio is [O], the carbon content is [C], and the nitrogen content is [N], the following formulas 1 to 3 are satisfied: Formula 1: [O]>[C]>[N], Formula 2: [O] ≥ 1.5 × [N], Formula 3: [C]≥1.5×[N].

8. An R-T-B system sintered magnet, characterized in that: Contains R2T 14 B compound and a grain boundary phase located at the grain boundary portion of the main phase, wherein R is a rare earth element and must include at least one selected from Nd, Pr and Ce, T is at least one of the transition metals and must include Fe, The R2T as the main phase of the R-T-B system sintered magnet 14 The average grain size of the B phase is 3 μm or more and 7 μm or less, and the R-T-B system sintered magnet contains oxygen, carbon and nitrogen. The oxygen content is 1000 ppm or more and 3500 ppm or less by mass ratio. The nitrogen content is 50 ppm or more and 600 ppm or less by mass ratio. The grain boundary phase has a rare earth oxide phase, The rare earth oxide phase includes a rare earth oxynitride phase having a NaCl type crystal structure, When the content (atomic %) of O in the rare earth oxynitride phase is {O} and the content (atomic %) of N in the rare earth oxynitride phase is {N}, the relationship of {O}>1.8×{N} is satisfied.

9. The R-T-B system sintered magnet according to claim 8, characterized in that: When the content (atomic %) of C in the rare earth oxynitride phase is represented by {C}, the relationship of {C}>{N}×0.5 is satisfied.

10. The R-T-B system sintered magnet according to claim 8 or 9, characterized in that: The ratio of the area of ​​the rare earth oxynitride phase to the area of ​​the rare earth oxide phase is greater than 50%.

11. The R-T-B system sintered magnet according to claim 8 or 9, characterized in that: The portion includes a portion where at least one of the Tb concentration and the Dy concentration gradually decreases from the magnet surface toward the inside of the magnet.

Citation Information

Patent Citations

  • Production of rare earth magnet

    JP1996148317A

  • Manufacture of raw material powder for rare-earth magnet

    JP1994140220A

  • Manufacture of rear-earth permanent magnet

    JP1998022154A

  • R-t-b based rare earth permanent magnet

    JP2006100847A

  • Molded rare-earth magnet and process for producing same

    WO2011030635A1